Intellectual capital, social capital and collective intelligence - Napoleone, Luciana Maria; Conceição Camargo, Emília da; dos Santos, Emanoel Vitorino; Céu Bertonazzi, Sônia Regina (Qualitative and Quantitative Methods in Libraries, 2019)
An exploratory analysis with qualitative focus combines examples of "out of box" legal researches with theoretical references on intellectual capital, social capital and collective intelligence. The analysed data consists of real cases, sellected from an exploratory qualitative study, on January and February 2016, mainly from São Paulo city, Brazil. This investigation has identified: (1) intellectual capital, produced by librarians and researchers, as products of their surveys; (2) existing social capital among Law librarians, expressed by means of their information research and diffusion, articulated throughout social media, discussion lists and networking; (3) collective intelligence, indicated by mapping information sources and survey strategies by means of cooperation and sharing.